Raising Legal Awareness in MSME Trade: Protecting and Registering Trademarks - Siagian, Putri Rumondang; Desiandri, Yati Sharfina; Saidin, Saidin; Shauqi, Saddam; Wau, Hilbertus Sumplisius M.; Azwar, T. Keizerina Devi (Faculty of Law, Andalas University, 2025)
Micro, Small, and Medium Enterprises (MSMEs) as small-scale industries tend to ignore the importance of intellectual property protection, particularly evident in the minimal registration of MSME trademarks with the Directorate General of Intellectual Property. Although the World Intellectual Property Rights (WIPO) recognizes the potential of MSMEs to drive product innovation and creativity, MSME awareness of the use of Intellectual Property Rights remains low. This study uses a normative legal research method, focusing on the study of legal provisions related to MSME trademark registration and protection. A descriptive analytical approach is used to identify and resolve existing legal issues, with reference to relevant laws and regulations. Trademark registration is considered the basis for rejecting similar trademarks filed by other parties for similar goods or services. The